Studying Opera Works by Russian Composers as a Way of Forming Musical Dramaturgy and Stage Skills in Music School Students - Okhunjon Kimsanov; Sardor Shodmonzoda (Bright Mind Publishing, 2025)
The study of operatic works by Russian composers plays a crucial role in the formation of musical dramaturgy and stagecraft skills among students of music schools. Russian opera, characterized by its rich musical and dramatic structure, provides students with an opportunity to explore the intricate relationship between music and theatrical performance. This study examines how exposure to operatic masterpieces enhances students’ understanding of dramatic expression, vocal technique, and stage presence. Special attention is given to the pedagogical benefits of integrating Russian opera into music school curricula, emphasizing its role in developing interpretative skills, emotional depth, and musical storytelling. Furthermore, the research highlights how engagement with operatic works fosters a comprehensive approach to performance, helping students bridge the gap between vocal artistry and theatrical expression. The findings suggest that Russian opera serves as an effective educational tool, allowing students to cultivate essential skills for both musical and stage performance.
Keywords: Russian opera, musical dramaturgy, vocal technique, stage performance, interpretative skills, theatrical expression, character development, emotional depth, music education, operatic training.